2017
DOI: 10.1002/imhj.21661
|View full text |Cite
|
Sign up to set email alerts
|

Does Training in the Circle of Security Framework Increase Relational Understanding in Infant/Child and Family Workers?

Abstract: This article evaluated whether attendance at Circle of Security training workshops resulted in attendees showing greater empathy and attachment-related knowledge and understanding, and fewer judgmental responses to viewing a stressful parent-child interaction. Participants were 202 practitioners who attended and completed a 2-day (n = 70), 4-day (n = 105), or 10-day (n = 27) COS training workshop in Australia or New Zealand in 2015. In a pre/post design, participant reactions to a video clip of a challenging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Our finding that training in the Circle of Security model resulted in participants bringing a more relational understanding to their work with the parent–child dyad is similar to the findings from McMahon et al. (2017) and Avery et al. (2008), who reported that after training, participants took a more relational perspective of a challenging parent–child interaction than they had prior to COS‐P training.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding that training in the Circle of Security model resulted in participants bringing a more relational understanding to their work with the parent–child dyad is similar to the findings from McMahon et al. (2017) and Avery et al. (2008), who reported that after training, participants took a more relational perspective of a challenging parent–child interaction than they had prior to COS‐P training.…”
Section: Discussionsupporting
confidence: 87%
“…McMahon, Huber, Kohlhoff, and Camberis (2017) replicated a previous study by Avery, Matthews, Hoffman, Powell, and Cooper (2008) that examined the impact of COS‐P training on practitioners understanding and application of the concepts of the program. Both studies provided similar results and found that after completing COS‐P training, the practitioners' understanding and perception of a video clip of a challenging child–parent interaction showed a significantly greater understanding of attachment concepts after training.…”
mentioning
confidence: 61%
“…Despite the popularity and pervasive uptake of the COS-P, evidence about its effectiveness remains limited (Kohloff et al, 2016;Nielsen et al, 2020) with a recognition of the need for more research (McMahon et al, 2017). Two small-scale studies, each with 15 participants, suggested promising results such as increase in parental reflective functioning, decrease in caregiving helplessness and reduction in anger/rejection toward child (Kohloff et al, 2016); significant improvement in discipline practices; and small mean improvements in emotion regulation and positive parent attributions and improvement in discipline practices (Horton & Murray, 2015).…”
Section: Cos Interventionmentioning
confidence: 99%
“…The centerpiece of both versions is a simple graphic ( Figure 1 ), which captures the core dynamic at the heart of attachment theory regarding the child's need for both connection and exploration, and the caregiving behaviors that support these needs ( 11 – 13 ). Also fundamental to both versions is the therapeutic relationship between facilitator and participants ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…COS-P is broadly disseminated in North America, Europe, and Asia, and has proved particularly popular in Australia, where more than 10,000 COS-P facilitators had been trained by late 2016 ( 14 ). This figure will now be substantially higher, with more than 10 official COS-P training courses held around the country each year, often training more than 200 individuals at a time.…”
Section: Introductionmentioning
confidence: 99%